Rotační stabilita kolenního kloubu 2 roky po rekonstrukci anterolaterálního ligamenta společně s rekonstrukcí LCA: biomechanická studie - Komzák, M; Hart, R; Náhlík, D; Vysoký, R (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
PURPOSE OF THE STUDY Knee injuries accompanied by anterior cruciate ligament (ACL) tears can also result in rotational instability of the joint. Subsequent insufficient rotational stability after the ACL reconstruction can be a direct consequence also of injuries to lateral knee structures, specifically the anterolateral ligament (ALL). This residual postoperative rotational instability may be prevented by multiple surgical techniques. The purpose of this study was (1) to evaluate the knee stability in internal rotation after the "anatomical" single-bundle (SB) anterior cruciate ligament reconstruction together with ALL reconstruction compared to the double-bundle (DB) ACL reconstruction two years after surgery; (2) to compare the knee joint stability after the ACL and ALL reconstruction with the healthy contralateral knee joint. MATERIAL AND METHODS All the measurements were conducted by the computer navigation system. The study included 20 patients after the single-bundle ACL and ALL reconstruction and 20 patients after the double-bundle ACL reconstruction. The follow-up examination was carried out at 25 months after surgery on average (24 months at least). All measurements were performed in both the healthy and operated knee. Once the data necessary for navigation were determined, the patient remained in standing position with both feet firmly placed on the mat with intermalleolar distance of 20 cm. Then, at 30-degree flexion of the knee joints, the patient first performed the joint internal rotation by trunk torsion, followed by external rotation. Each measurement was repeated 3 times. A non-parametric t-test was used for statistical processing. RESULTS The mean internal rotation in the injured knee joint was 19.1 degrees preoperatively and 8.1 degrees postoperatively, while in the healthy knee it was 8.4 degrees. External rotation was not assessed. The reported internal rotation in the knees after DB ACL reconstruction was 9.2 degrees (p ≥ 0.05). DISCUSSION The double-bundle ACL reconstruction is a complex technique that can lead to many intraoperative and postoperative complications. Grafts harvested from both hamstrings can have an effect on the rotational stability of the joint. In order to restore the knee rotational stability with fewer potential complications, the method of choice can be the ACL reconstruction using the quadriceps femoris muscle graft and the ALL reconstruction using the gracilis muscle graft, leaving the semitendinosus tendon intact. CONCLUSIONS The obtained values reveal that the single-bundle ACL reconstruction in combination with ALL reconstruction results in the same internal rotational stability in the knee joint as the double-bundle ACL reconstruction. Similar joint rotational stability is observed in all the knee joints reconstructed with the use of these techniques and in the contralateral healthy knee joint. Key words: anterolateral ligament, anterior cruciate ligament, internal rotational stability, objective measurement.
Keywords: poranění předního zkříženého vazu; Anterior Cruciate Ligament Reconstruction; Joint Instability; Range of Motion, Articular; mrtvola; biomechanika; lidé; rozsah kloubních pohybů; Knee Joint; Anterior Cruciate Ligament Injuries; kolenní kloub; Cadaver; Biomechanical Phenomena; nestabilita kloubu; rekonstrukce předního zkříženého vazu; Humans